2015
DOI: 10.1002/ceas.12014
|View full text |Cite
|
Sign up to set email alerts
|

From School Counselor to Counselor Educator: A Phenomenological Study

Abstract: Through a phenomenological study, the experiences of 8 early-career school counselor educators who entered academia directly from positions as P-12 school counselors were examined. Results revealed that the participants experienced numerous challenges and supports related to their transition. Recommendations for counselor educators, doctoral students, and new faculty are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…That the instructional component did not directly affect research self‐efficacy or scholarly productivity seems to contradict reports that faculty need and request more training in research, more mentorship, and more assistance in research (e.g., Briggs & Pehrsson, 2008; Milsom & Moran, 2015; Okech et al, 2006). An expert panel in a Delphi study on developing research competencies suggested that competency includes continued development and education around research (Wester & Borders, 2014).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…That the instructional component did not directly affect research self‐efficacy or scholarly productivity seems to contradict reports that faculty need and request more training in research, more mentorship, and more assistance in research (e.g., Briggs & Pehrsson, 2008; Milsom & Moran, 2015; Okech et al, 2006). An expert panel in a Delphi study on developing research competencies suggested that competency includes continued development and education around research (Wester & Borders, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…The push for research, and ultimately scholarly productivity, at the larger institutional levels comes at a time when counselor educators are stating the need for more research training (Milsom & Moran, 2015; Okech, Astramovich, Johnson, Hoskins, & Rubel, 2006). Department chairs in counselor education have questioned the quality of research training of faculty applicants (Barrio‐Minton, Myers, & Morganfield, 2012; Lambie, Rubel, Smith, Spurgeon, & Wester, 2015), whereas counselor education faculty have stated that their research needs are not being met by colleagues within their department (Briggs & Pehrsson, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies of untenured minoritized counselor educators (Casado Pérez & Carney, 2018;Haskins et al, 2016), participants described marginalization and oppression as well as devaluation of their research. Other authors (e.g., Briggs & Pehrsson, 2008;Milsom & Moran, 2015) found that new counselor educators were particularly stressed about their research and writing, often citing high teaching and service responsibilities (Bradley, 2005; N. R. Hill, 2004;Shillingford, Trice-Black, & Butler, 2013). In a unique sequence of studies across 6 years, Magnuson and colleagues (Magnuson, 2002;Magnuson et al, 2006;Magnuson, Norem, & Lonneman-Doroff, 2009;Magnuson, Shaw, Tubin, & Norem, 2004) broadly investigated new counselor educators' sources of satisfaction, dissatisfaction, pleasure, and disappointment.…”
mentioning
confidence: 99%